Heavy Metal Content in Chicken Meat Products: A Health Risk Assessment Study - M. A. Morshdy, Alaa Eldin; M. El Bayomi, Rasha; M. Khalifa, Sahar; M. Salah El-Dien, Waiel; Darwish, Wageh; Fikry A. Mahmoud, Abdallah (Journal of Advanced Veterinary Research, 2022)
There is an increasing demand for chicken meat products due to their high nutritive value, specific aroma and flavor, and cheap price compared to red meat. However, there is a clear lack of information on the residual content of toxic metals such as lead (Pb), cadmium (Cd), mercury (Hg), and trace elements such as zinc (Zn), and copper (Cu) in such products. Therefore, this study was undertaken to estimate the residual contents of Pb, Cd, Hg, Zn, and Cu in five chicken meat products including chicken burger, chicken fillet, chicken luncheon, chicken nuggets, and chicken panne. Moreover, estimated daily intakes (EDI), and the potential health risks of heavy metals due to consumption of such meat products were calculated for Egyptian adults and children. The achieved results indicated no detection of Hg in any sample. However, the other measured elements were detected in all examined chicken meat product samples at variable concentrations. The chicken burger had the highest metal concentrations. Several samples had higher Pb and Cd levels than the set maximum permissible limits. However, the calculated EDI, hazard ratio, and hazard index revealed no potential risks associated with the consumption of such chicken meat products among Egyptian adults and children.